Functionalizing Ferritin Nanoparticles for Vaccine Development - Margarida Q. Rodrigues; Paula M. Alves; António Roldão (MDPI AG, 2021)
In the last decade, the interest in ferritin-based vaccines has been increasing due to their safety and immunogenicity. Candidates against a wide range of pathogens are now on Phase I clinical trials namely for influenza, Epstein-Barr, and SARS-CoV-2 viruses. Manufacturing challenges related to particle heterogeneity, improper folding of fused antigens, and antigen interference with intersubunit interactions still need to be overcome. In addition, protocols need to be standardized so that the production bioprocess becomes reproducible, allowing ferritin-based therapeutics to become readily available. In this review, the building blocks that enable the formulation of ferritin-based vaccines at an experimental stage, including design, production, and purification are presented. Novel bioengineering strategies of functionalizing ferritin nanoparticles based on modular assembly, allowing the challenges associated with genetic fusion to be circumvented, are discussed. Distinct up/down-stream approaches to produce ferritin-based vaccines and their impact on production yield and vaccine efficacy are compared. Finally, ferritin nanoparticles currently used in vaccine development and clinical trials are summarized.